In Step 6, the equation is ...
-12 = x - 36
In step 7, the equation is ...
-12 +36 = x -36 +36
Clearly, to get to step 7, 36 has been added to both sides of the equation.
Adding 36 to both sides of the equation is justified by ...
... C) Addition Property of Equality
_____
<em>More about the addition property of equality</em>
The addition property of equality says you can add the same value to both sides of an equation without changing the values of the variables that make the equation true. Here, x=24 makes the equation of step 6 true, and x=24 makes the equation of step 7 true.
Answer:
y varies of directly as x. This means that the equation is of the form y=kx where k is any number.
Substituting y=12 when x=4, we get
12=k×4⇒k=3
Hence, the required equation is y=3x.
The value of y when x=5 is y=3x5=15.
Step-by-step explanation:
bro it will work ♥️
Answer:36 dad 9 charley
Step-by-step explanation:
Answer: This is how I would do it 8x67=402
Step-by-step explanation:
You know that the two triangles are congruent because two sides and one angle are congruent.
According to CPCTC, corresponding parts of congruent triangles are congruent, which means that PR and SU are equal.
3y-2=y+4
3y=y+6
2y=6
y=3
3(3)-2=9-2=7
7+4+6=17
The perimeter is 17 feet.
Hope this helps!